Choice‐Based Reminder Cues: Findings From an mHealth Study to Improve Tuberculosis (TB) Treatment Adherence Among the Urban Poor in India. Issue 2 (2nd June 2020) - Das Gupta, Debasree; Patel, Amit; Saxena, Deepak; Koizumi, Naoru; Trivedi, Poonam; Patel, Krupali; Raval, Devang; King, Andrew; Chandler, Kerianne
Abstract : Poor treatment outcomes due to nonadherence and consequent high levels of drug resistance continue to challenge efforts to combat tuberculosis (TB) in India. Mobile health‐ or mHealth‐based reminder cues have been considered in multiple health behavior modification interventions, including TB treatment nonadherence. We conducted a quasi‐experimental study in Ahmedabad, India, to examine the effectiveness of mHealth‐based reminder cues customized to meet diverse patient needs. Results from this experiment indicate that the potential of customized mHealth reminder cues may remain unrealized unless addressed in conjunction with the multifaceted drivers of TB treatment nonadherence. The perspective we present here has broad relevance for future mHealth studies, especially in interpreting challenges that arise within resource‐scarce settings of the urban poor and prevent them from adhering to recommended TB treatment regimens. Abstract : Los malos resultados del tratamiento debido a la falta de adherencia y los consecuentes altos niveles de resistencia a los medicamentos continúan desafiando los esfuerzos para combatir la Tuberculosis (TB) en la India. Las señales de recordatorio móviles basadas en salud o mHealth se han considerado en múltiples intervenciones de modificación del comportamiento de la salud, incluida la no adherencia al tratamiento de la TB. Realizamos un estudio cuasiexperimental en Ahmedabad, India, para examinar la efectividad de las señales recordatorias basadas en mHealth personalizadas para satisfacer las diversas necesidades de los pacientes. Los resultados de este experimento indican que el potencial de las señales recordatorias personalizadas de mHealth puede permanecer sin realizarse a menos que se aborde en conjunto con los impulsores multifacéticos de la no adherencia al tratamiento de la TB. La perspectiva que presentamos aquí tiene una gran relevancia para futuros estudios de mHealth, especialmente en la interpretación de los desafíos que surgen en entornos de escasos recursos urbanos de los pobres urbanos y evitan que se adhieran a los regímenes de tratamiento de TB recomendados. Abstract : 由不依从治疗和继而产生的强耐药性导致的治疗结果不佳持续对印度为打击结核病(TB)所做的努力发起挑战。基于移动医疗(Mobile health, 简称mHealth)的提示信息被考虑纳入多个调整医疗行为的干预手段, 包括TB治疗不依从性。我们在印度艾哈迈达巴德市进行了一项准实验研究, 检验被用于满足不同患者需求而定制的移动医疗提示信息所产生的效果。实验结果显示, 个性化移动提示信息的潜能可能依然不会实现, 除非与TB治疗不依从性的多面驱动因素一同发挥作用。我们在此提出的观点对未来移动医疗研究具有广泛相关性, 尤其是用于诠释城市贫困人群资源稀缺背景下产生的挑战, 后者阻碍了贫困人群坚持使用推荐的TB治疗方法。